A survey of post-amputation pains in serving military personnel. Issue 1 (13th July 2013) - Aldington, Dominic; Small, C; Edwards, D; Ralph, J; Woods, P; Jagdish, S; Moore, R A
Abstract : Introduction: Amputation is a common injury in survivors of current military conflicts. The primary aim of this study was to establish the prevalence rate of phantom limb pain (PLP) in military personnel undergoing rehabilitation at the UK's Defence Medical Rehabilitation Centre. The secondary aims were to establish treatment failure rates and prevalence rates of phantom limb sensations (PLS) and residual limb pains (RLP). Method: A questionnaire survey was developed from that used in a previous study of pains in veterans. Questions were asked of the intensity of PLP, RLP and PLS over the previous month and the entire time since amputation. Treatment failure was defined as greater than 'mild' pain. A literature review for similar studies was undertaken. Results: There were 48 responders with 65 amputations. PLP in the previous month was reported by 49% of respondents and 20% were classed as treatment failures; 76% had PLP at some point and 56% were analgesic failures. PLS was commoner with 70% reported over the previous month and 66% at any time. 65% had RLP over the previous month, 31% were treatment failures and 80% had experienced RLP at some point and 63% of these were failures of treatment. Eight other papers were found for comparison. Conclusions: This is the first paper that describes prevalence of pains associated with amputation in a serving military population. It also describes the use of analgesic failure as a concept and provides an encouraging rate of as low as 20% in this population.